PENGARUH KUALITAS SDM, SISTEM PENGENDALIAN INTERN, DAN PENGAWASAN KEUANGAN DAERAH TERHADAP NILAI INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH PADA ORGANISASI PERANGKAT DAERAH KOTA PEKANBARU - Sumardi, Heru; Diana, Haugesti (Journal Of Islamic Finance And Accounting Research, 2023)
The purpose of this study was to examine the effect of the quality of human resources, internal control systems and regional financial supervision on the information value of local government financial reports at the Pekanbaru City OPD. This type of research is descriptive quantitative research with the object of research being the Pekanbaru City OPD. The research sample totaled 59 OPD employees in Pekanbaru using a purposive sampling technique for sampling. The data used is primary data in the form of a research questionnaire. The data analysis technique used is multiple linear regression with the help of SPSS Version 26. The results of the research partially and simultaneously show that the quality of human resources, internal control systems and regional financial supervision have a significant effect on the information value of local government financial reports at the Pekanbaru City Regional Apparatus Organization.